Scale Models and Postmodernism: Revisiting Idea as Model (1976–81). Issue 3 (1st September 2020) - Vervoort, Stefaan
Abstract: In 1976–77 the Institute for Architecture and Urban Studies (IAUS) in New York organised Idea as Model, an exhibition of architectural models realised by 22 architects and architects' teams. Many participants can be considered protagonists of postmodern architecture, including Michael Graves, John Hejduk, Robert Stern and Stanley Tigerman, Mario Gandelsonas, Léon Krier, Charles Moore, Massimo Scolari and Oswald Mathias Ungers. This article revisits Idea as Model in relation to then-raging discussions regarding the use of models and drawings in modernism and postmodernism and the debates about the respective "limits" of architecture and art. Framed as a response to architecture shows in New York and as a product of the aims of then-IAUS director Peter Eisenman, Idea as Model is described both as characteristic of postmodernism and as reverberating with the long-standing suspicion among architects over the ambiguities of the scale model.